Wireless communication through reconfigurable intelligent surfaces with multi-antenna energy harvesting - Alanazi, Faisal (Signal, image and video processing, 2021)
The paper derives the throughput of wireless communications using reconfigurable intelligent surfaces (RIS) with energy harvesting. The base station (BS) harvests energy using radio frequency signals received from node A over n r antennas. The harvested energy is used to transmit data to N users. We optimize harvesting duration to maximize the throughput. We also suggest the use of two RIS. The first RIS is placed between node A and BS to improve the energy harvesting process. The second RIS is placed between BS and users so that all reflections have the same phase at each user. A set of reflectors is dedicated to each user. We show that wireless communication with eight and sixteen reflectors dedicated to a given user offers 12 and 18 dB gain with respect to wireless communications with energy harvesting and without RIS. The proposed wireless communications with two RIS with eight reflectors offer 27 dB gain with respect to wireless communications without RIS.